Continuous Visible‐Light Photoflow Approach for a Manganese‐Catalyzed (Het)Arene C−H Arylation. (3rd July 2018) - Liang, Yu‐Feng; Steinbock, Ralf; Yang, Long; Ackermann, Lutz
Abstract: Manganese photocatalysts enabled versatile room‐temperature C−H arylation reactions by means of continuous visible‐light photoflow, thus allowing for efficient C−H arylations in 30 minutes with ample scope. The robustness of the manganese‐catalyzed photoflow strategy was shown by visible light‐induced gram‐scale synthesis, clearly outperforming the batch performance.